Analisis Wacana Kritis pada Malaka Podcast: Implikasi RUU TNI dan Kontrol Sipil - Tamami, Sulthan Zaidan; Muktiyo, Widodo; Anshori, Mahfud (Jurnal Audiens, 2025)
The government is endeavoring to establish policies that legitimize the participation of TNI (Indonesian National Armed Forces) and Police personnel in practical politics. This endeavor is undertaken without adherence to democratic principles, and the legislative process is also non-transparent. Malaka Podcast, a discussion platform and learning medium for youth, produced an episode titled “Don’t Let Indonesia Regress to the Dark Ages.” The podcast featured legal experts to discuss the re-emergence of the ABRI dwifungsi (dual function) discourse, an attempted revival under the current regime. This research aims to deconstruct the dialogue within this podcast using Teun A. van Dijk's critical discourse analysis (CDA). The dialogue content was thematically coded, derived from the podcast transcript and the researcher's thorough engagement with the entire audio. Subsequently, these thematic codes were analyzed within the dimensions of context, social cognition, and ideology, in accordance with Van Dijk's CDA framework. The findings conclude that the podcast dialogue is imbued with pro-democracy messages, the importance of civil society solidarity, and critiques of the law-making process.